Technology diffusion and the stability of climate coalitions - Richard S. J. Tol; Wietze Lise; Bob van der Zwaan (Fondazione Eni Enrico Mattei (FEEM), 2000)
Free-riding is a major problem for international climate policy. A country can take advantage of other countries' emission reduction without contributing to abatement policies itself. Game theory suggests that issue linkage may help to overcome free-riding. Earlier studies suggest that if negotiations on greenhouse gas emission reduction are coupled to negotiation on technology transfer, the incentives to co-operate increase. This study confirms that finding. A country has less reason to free-ride if free-riding implies that the countries loses access to desirable, foreign technologies. We also show that, in many cases, it hurts to deny another country access to domestic technologies, if that country retaliates by withholding its technologies. We further show that the losses of withholding abatement technologies are small relative to the gains of free-riding. So, linking greenhouse gas emission reduction with technology diffusion helps to deter free-riding, but only a little bit, and only if the two issues are automatically linked.
Keywords: 330; Klimaschutz; Internationale Umweltpolitik; Trittbrettfahrerverhalten; Technologietransfer; Spieltheorie; Theorie